Financial Management Behavior in Indonesia: Gender Perspective - Nur Ariani Aqidah; Hamida Hamida (Owner : Riset dan Jurnal Akuntansi, 2025)
This study aims to compare financial behavior between unmarried working men and women. This research used a purposive sampling technique with a total of 100 respondents. To achieve the research objectives, this research uses quantitative methods with independent sample t test data analysis. The research results show that there is no difference in the financial behavior of unmarried working men and women in Indonesia. This research shows that individual financial behavior is determined by how individuals gain financial knowledge and self-control in financial management. The limitations of this research are this research uses a sample of unmarried working men and women in Indonesia so it cannot be generalized to other countries. Second, this research does not use control variables that influence financial management behavior such as Financial Attitude, Financial Knowledge, and Locus of Control.